2019
DOI: 10.1002/ppul.24256
|View full text |Cite
|
Sign up to set email alerts
|

Association between air pollution and sleep disordered breathing in children

Abstract: Background and Objective Similar to other respiratory diseases, sleep disordered breathing (SDB) may be exacerbated by air contaminants. Air pollution may have an impact on incidence and severity of SDB in children. The aims of this study were to examine potential associations between the exposure to different air pollutants and SDB symptoms in children. Methods In this cross‐sectional study, parents from first grade children of elementary schools throughout Chile were included. Data about clinical and family‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Our findings are also consistent with previous research [23,26,28,38], which found that increasing levels of ozone and PM 10 were associated with a reduction in sleep efficiency [23], an increase in sleep–disordered breathing (SDB) [23,26,28], and an increase in the severity of sleep apnea [38]. In a recent study across seven northeastern Chinese cities, higher long-term exposure to PM 2.5 , PM 10 , SO 2 , NO 2, and O 3 was associated with a 1.02–1.53 greater odds ratio (OR) of sleep disorders in Chinese children [39].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are also consistent with previous research [23,26,28,38], which found that increasing levels of ozone and PM 10 were associated with a reduction in sleep efficiency [23], an increase in sleep–disordered breathing (SDB) [23,26,28], and an increase in the severity of sleep apnea [38]. In a recent study across seven northeastern Chinese cities, higher long-term exposure to PM 2.5 , PM 10 , SO 2 , NO 2, and O 3 was associated with a 1.02–1.53 greater odds ratio (OR) of sleep disorders in Chinese children [39].…”
Section: Discussionsupporting
confidence: 94%
“…To our knowledge, only a few studies have examined the relationship between air pollution and sleep duration. Previous studies have focused primarily on the effect of air pollution on sleep-related respiratory symptoms such as sleep-disordered breathing [23,26,27,28], obstructive sleep apnea (OSA), and sleep apnea [29,30]. However, to our knowledge, no study has examined the relationship between ambient air pollution and sleep duration.…”
Section: Introductionmentioning
confidence: 99%
“…16 Air pollutants such as particulate matter, ozone (O 3 ) and nitrogen dioxide all have adverse effects on the airways. 17 An association between exposure to air pollutants and snoring have been reported in children 18 19 and habitual snoring was associated with having a bedroom with traffic noise but not to high exposure to traffic pollution in a Nordic population study . 20 In another study, exposure to O 3 was associated with an increase in AHI.…”
Section: Introductionmentioning
confidence: 95%
“…Outdoor air pollution is mainly associated with negative respiratory health outcomes [28]. Specific air pollutants were found to be linked to sleep disordered breathing in children, such as wheezing and snoring [29]. Inadequate sleep is associated with many other health problems, such as heart disease [30] and obesity [31].…”
Section: Outdoor Air Pollutionmentioning
confidence: 99%